2018
DOI: 10.1080/09546634.2018.1506079
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new synthetic xerogel nanoparticles of silver and zinc oxide against causative agents of dermatophytoses

Abstract: Xerogel nanoparticles composed of Ag and ZnO were successfully prepared. They had antidermatophytic action in specific concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…14 Dermatophytoses: Al Janabi et al observed xerogel nanoparticles composed of ZnO had antidermatophytic action in specific concentrations. 15 In the study, 30 patients with tinea corporis received topical 10% zinc sulfate solution twice daily for two months, complete cure response was observed in 13 (43.33%) patients, partial response in 7 (23.34%) patients and no response in 10 (33.33%) patients while in placebo group the clinical response was two (6.67 %) patients with partial improvement and 28 (93.33%) patients with no improvement. 16 Bromhidrosis: Foot odor is a common sociomedical problem that affects the feet of human beings of different etiological factors.…”
Section: Zinc As a Therapymentioning
confidence: 97%
“…14 Dermatophytoses: Al Janabi et al observed xerogel nanoparticles composed of ZnO had antidermatophytic action in specific concentrations. 15 In the study, 30 patients with tinea corporis received topical 10% zinc sulfate solution twice daily for two months, complete cure response was observed in 13 (43.33%) patients, partial response in 7 (23.34%) patients and no response in 10 (33.33%) patients while in placebo group the clinical response was two (6.67 %) patients with partial improvement and 28 (93.33%) patients with no improvement. 16 Bromhidrosis: Foot odor is a common sociomedical problem that affects the feet of human beings of different etiological factors.…”
Section: Zinc As a Therapymentioning
confidence: 97%
“…246 Xerogel formed of Ag NPs and ZnO NPs exhibited satisfactory susceptibility against Trichophyton mentagrophytes and Trichophyton verrucosum, dermatophyte fungi that often cause a superficial skin disease called dermatophytosis. 247 ZnO NP− lignin aggregates showed significant antifungal activity against selected fungal strains like Aspergillus fumigatus, Aspergillus penicilloides, C. albicans, Conidiobolus coronatus, and Microsporum cookei. 248 The 40 nm ZnO NPs synthesized by a conventional chemical procedure demonstrated antifungal action on strains of Aspergillus niger and Botrytis cinerea, being more efficient in inactivating B. cinerea.…”
Section: Antibacterial Applicationsmentioning
confidence: 99%
“…In this context, Alhazmi and colleagues proved that 25 nm ZnO NPs synthesized by precipitation method showed an impactful antifungal effect against isolates of azole-resistant Aspergillus flavus . Xerogel formed of Ag NPs and ZnO NPs exhibited satisfactory susceptibility against Trichophyton mentagrophytes and Trichophyton verrucosum, dermatophyte fungi that often cause a superficial skin disease called dermatophytosis . ZnO NP–lignin aggregates showed significant antifungal activity against selected fungal strains like Aspergillus fumigatus, Aspergillus penicilloides, C.…”
Section: Antimicrobial Applicationsmentioning
confidence: 99%
“…Although it is located far from impact area of the organism's defense systems, the inefficacy of the immune and other defense systems plays an important role in the arise of the disease (Lagowski et al, 2019). Besides, the humidity rate of the region, the deterioration of the keratinized tissue in the epidermis layer of the skin, zinc, vitamin A and D deficiencies are also important factors in the arise of the cases (Al-Janabi and Bashi, 2018;Çifci, 2018).…”
Section: Introductionmentioning
confidence: 99%